2014
DOI: 10.1155/2014/432529
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Bottom Friction Coefficient in the Bohai, Yellow, and East China Sea

Abstract: The adjoint tidal model based on the theory of inverse problem has been applied to investigate the effect of bottom friction coefficient (BFC) on the tidal simulation. Using different schemes of BFC containing the constant, different constant in different subdomain, depth-dependent form, and spatial distribution obtained from data assimilation, the M2constituent in the Bohai, Yellow, and East China Sea (BYECS) is simulated by assimilating TOPEX/Poseidon altimeter data, respectively. The simulated result with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 23 publications
3
28
0
Order By: Relevance
“…Previous studies have suggested an inverse relationship between Cd and water depth to be used by numerical models (e.g., Wang et al, 2014;Yang et al, 1994). In the ECSS, Lv and Zhang (2006) estimated the spatial distribution of Cd using an adjoint model that assimilated sea levels observed by satellite altimeters.…”
Section: Impacts Of Currents and Waves On Bottom Drag Coefficientmentioning
confidence: 99%
“…Previous studies have suggested an inverse relationship between Cd and water depth to be used by numerical models (e.g., Wang et al, 2014;Yang et al, 1994). In the ECSS, Lv and Zhang (2006) estimated the spatial distribution of Cd using an adjoint model that assimilated sea levels observed by satellite altimeters.…”
Section: Impacts Of Currents and Waves On Bottom Drag Coefficientmentioning
confidence: 99%
“…Tidal resonance can develop within a semi‐enclosed basin, such as the Gulf of California, the Adriatic Sea, the Persian Gulf, or the Bay of Fundy (Longhitano et al., ; Martinius & Gowland, ; Reynaud & Dalrymple, ; Roos & Schuttelaars, ; Shaw et al., ; Sztanó & de Boer, ), if the length of the embayment approaches an odd multiple of a quarter of the tidal wavelength (Godin, ; Sztanó & de Boer, ; Yoshida et al., ):L=T×g×dwhere L is the tidal wavelength, T the period of the M2 tide (44′712 s; Roos & Schuttelaars, ), g the gravitational acceleration (9.81 m/s 2 ), and d the water depth. However, such resonant behaviour depends also upon the basal shear stresses and the subaqueous morphology of the tidal system (Roos & Schuttelaars, ; Wang, Liu, & Lv, ).…”
Section: Discussionmentioning
confidence: 99%
“…where L is the tidal wavelength, T the period of the M2 tide (44′712 s; Roos & Schuttelaars, 2011), g the gravitational acceleration (9.81 m/s 2 ), and d the water depth. However, such resonant behaviour depends also upon the basal shear stresses and the subaqueous morphology of the tidal system (Roos & Schuttelaars, 2011;Wang, Liu, & Lv, 2014). For water depths d of approximately 20 and 25 m (Equation 1), the tidal wavelength L approaches approximately 625 or 700 km, respectively, which gives a quarter wavelength of approximately 156 or 175 km, respectively.…”
Section: Facies Distribution Energy Levels Basin Geometry and Tidmentioning
confidence: 99%
“…To avoid spurious reflection of waves in the domain, open boundary conditions are optimized based upon the adjoint method (Sasaki et al, ; Shulman et al, ) by iterating the water level input at the open boundary until the deviation between observed and modeled water levels at HM5 is minimized. The adjoint method is widely used in oceanography studies to optimize open boundary forcings in hydrodynamic simulations of estuaries subjected to tidal (e.g., Blayo & Debreu, ; Seiler, ; Wang et al, ) and subtidal forcings (Liu & Gan, ). In this study, the control variables, that is, the variables with respect to which the optimization is run, are the amplitudes and phases of the main oscillation modes of the water level observed at HM5.…”
Section: Methodsmentioning
confidence: 99%